2007
DOI: 10.4067/s0716-97602007000200010
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the morphometry of the lungs and the mode of locomotion in birds and mammals

Abstract: We studied the lung diffusion parameters of two species of birds and two species of mammals to explore how structural and functional features may be paralleled by differences in life style or phylogenetic origin. We used two fast-flying species (one mammal and one bird), one running mammal and one bird species that flies only occasionally as models. The harmonic mean thickness of the air-blood barrier was very thin in the species we studied. An exception was the Chilean tinamou Notoprocta perdicaria, which onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…When we consider the oxygen diffusing capacity in the three species we observed that the larger species (Z. auriculata and M. melanoptera) have high values similar to those reported for Z. auriculata (Figueroa et al) (Canals et al, 2005b;Figueroa et al) we estimated the expected D t O 2 for our species. While for Z. auriculata and M. melanoptera D t O 2 were 82.7 ± 17.0% and 85.9 ± 2.5% of the expected value, for C. picui it was only 48.4 ± 18.5% of the expected value.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…When we consider the oxygen diffusing capacity in the three species we observed that the larger species (Z. auriculata and M. melanoptera) have high values similar to those reported for Z. auriculata (Figueroa et al) (Canals et al, 2005b;Figueroa et al) we estimated the expected D t O 2 for our species. While for Z. auriculata and M. melanoptera D t O 2 were 82.7 ± 17.0% and 85.9 ± 2.5% of the expected value, for C. picui it was only 48.4 ± 18.5% of the expected value.…”
Section: Discussionsupporting
confidence: 81%
“…In birds, the lung volume is lower than that of non-flying mammals, while bat lungs show the opposite trend. High respiratory surface density and a thin air-blood barrier have been reported in several small bird species, such as Sparkling Violater (Colibri coruscans) (Dubach, 1981) while the Orders containing non-flying birds or birds that fly occasionally (e.g., Sphenisciformes, and Galliformes or Struthioformes), appear to have a thicker blood-gas barrier than flying birds (Maina, 2002;Canals et al, 2007;Figueroa et al).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This capacity can be quantified morphologically by measuring the ratio of the diffusive surface area of the lung and the harmonic mean thickness of the blood-gas barrier, the anatomical diffusion factor (ADF). Birds and mammals using the same mode of locomotion have very similar ADF (31,48,60). The power required for locomotor modes such as swimming and running is less than for modes such as flapping flight.…”
mentioning
confidence: 98%
“…However, bats have the highest levels of hematocrit measured in mammals and may reach values above 70% in Tadarida brasiliensis and Miniopterus minor. Red blood cells are smaller (Figueroa et al, 2007) and hemoglobin has been found in higher concentrations (18-24 g/100ml blood), similar to that found in hummingbirds (Johansen et al, 1987). Consequently, bats have a transport capacity of oxygen in the blood of 25 to 30%.…”
Section: The Heartmentioning
confidence: 49%